First Au monolayer formation on Cu(110) surface. Issue 1 (November 2020) - Sbiaai, K.; Dardouri, M.; Fathi, A.; Arbaoui, A.; Hassani, A.; Eddiai, F.; El Azrak, A.; Hasnaoui, A.; Boughaleb, Y.
Abstract: We study in this work the growth of a gold monolayer on a Cu (110) surface thanks to the kinetic Monte Carlo method. We considered a coverage of 0.1% of the monolayer. Indeed, the growth of a monolayer is done through the intermediary of several diffusion processes. All activation energies for each process were calculated using the static method coupled with the KMC method. This coupling is established by the ABBM anisotropic bond breaking model. The study of the results obtained in the temperature range (100-300K) at different deposition rates shows the formation of small 1D islands and certain 2D islands at high temperature (280 k-300 K).